The Influence of Local Politics on Educational Decisions - Gary Bigham; Jan Ray (Arizona State University, 2012)
This ex post facto, causal-comparative research study examined student reading performance data within a school district before and after a school district-wide decision to alter the reading curriculum in response to local political pressure from parents.  Data analysis revealed that test scores dropped to a significantly lower level, especially for students who were economically disadvantaged, after the reading curriculum was altered.  This study underscores the importance of making data-driven, rather than politically-influenced, decisions related to pedagogy, curriculum, instruction, and assessment by educational leaders.